Thermal vibrations in the metallic glass Cu64Zr36. (10th November 2016) - Schönfeld, Bernd; Zemp, Jérôme; Stuhr, Uwe
Abstract: Neutrons with 14.7 and 34 meV energy were used to determine the elastic and inelastic part of the structure factor for the metallic glass Cu64 Zr36 at 250 K. Based on the temperature dependence of the elastic scattering between 150 K and RT, an average mean-square displacement ⟨ u 2 ⟩ = 0.027 ( 3 )   Å 2 at 250 K is obtained. The experimental scattering-vector dependence of inelastic scattering in reference to elastic scattering is found to be well described by the Debye model. Both results are supported by molecular dynamics simulations. A procedure is presented to separate the elastic part also in total x-ray scattering. This allows the smearing of structural information due to thermal vibrations to be eliminated.